WEB DESIGN AS A MEDIA FOR PROMOTION OF CAKE PRODUCTS IN “KISS” MSMEs USING AIDA+S METHOD - Setiyo Prihatmoko; Sumaryanto Sumaryanto; Kartika Ensevasari (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
KISS Semarang is an MSME located in Mangunharjo, established in 2010. “KISS” Semarang MSME has done media promotions by distributing brochures. However, it is not optimal in its promotional media. The author is interested in making promotional media by making a web design in the form of a catalog in order to attract product purchasing power and make it more efficient in its promotional media. Web design design refers to research that uses the AIDA+S analysis method: Attention, Interest, Desire, Action and Satisfaction. In this study, the authors set KISS Semarang as the research subject, the data obtained for research purposes using techniques such as interviews, observations, questionnaires and literature studies. Research and development methods (Research and Development) are research methods used to produce certain products, and test the effectiveness of these products. Research and development in industry is the spearhead of an industry in producing new products needed by the market. Almost 4% of the costs used for research and development, even for the pharmaceutical and computer industry is more than 4%. The results showed that in the field trial, the web design was included in the good category and was able to promote products. After the validation test and web revision have been carried out from the previous media, the web design is feasible to use and publish.